PERANAN WANITA JEPANG DALAM MENTRANSFER BAHASA KEPADA ANAK PADA KELUARGA CAMPURAN ETNIK BALI ? ORANG JEPANG DI BALI - Laksminy, Luh Putu (Jurnal Studi Jender SRIKANDI; Vol. 3, No. 2 Juli 2004)
he Role of Japanese Women in Transferring a Language to their children in the Intermarriage between Balinese and Japanese Women Couples? is one of social aspects in bilingualism. The role of Japanese women in this study is an implication of the parents strategies applied in raising the children, language choice in KCBJ D and KCBJ U in terms of language use, and factors that contribute their language choice. Through an intensive research, parents in KCBJ family choose strategies (1), (2), (7), and (8). As a result, there are Balinese (BB) and Japanese (BJp) language transference to their children, their children are multilingual for they can speak Balinese, Japanese, and Indonesian language so there is a language maintenance in the language use of the children, especially Balinese and Japanese. Domain factors and its social contexts, demography and dominant language of the community, ethnicity, speaker?s social background, gender, language function, and two others general factors, namely personal and attitudinal factors such as the attitudes of children?s immediate family, extended family, friends, teachers, and the society in general, give a great influence on their language choice. From its situational context point of view, the use of BB, BI, and BJp not only expressed social process among Balinese and Japanese speaker took part in that social interaction, but also expressed the speaker?s attitude and judgments, and the role of language functions in the situation.
Keywords: peranan wanita, strategi, pilihan bahasa, faktor